Comparison of corporate social responsibility programmes of large international and small national hotel operators in Southeast Asia - Ji, Min Sheng (2012)
Although the concept of Corporate Social Responsibility (CSR) has been introduced in 1979, the service industry has just recently begun to adopt CSR programmes. This study seeks to identify, compare and investigate the differences of CSR programmes in Phuket, Thailand as conducted by the Holiday Inn Phuket, which is managed by a large international hotel operator, the InterContinental Hotels Group (IHG), and the Centara Grand Beach Resort Phuket, which is managed by, a small national hotel operator, the Centara Hotels and Resorts Group (CHRG).